Relationships between sexual socialization influences and sexual behavior among adolescent in Malaysia - Tan, Soon Aun (2014)
In Malaysia, adolescents' sexual behaviors have contributed to several social problems such as teenage pregnancy, abandoned babies, risky sexual behavior and HIV/AIDS infection cases. This study aimed to determine the relationships between sexual socialization influences (parental, peer and media factors) and sexual behavior among adolescents in Malaysia. This study employed a quantitative research approach and correlational research design. The respondents of the study consisted of 442 school-going adolescents aged 16 to 17 years old, recruited by using convenience sampling technique. Instruments used in this study included Sexual Communication with Parents and Peers (Longmore, Eng, Giordano & Manning, 2009), Parental and Peer Approval of Sexual Behavior (Treboux & Busch-Rossnagel, 1990), Peer Norm Scale (Ball, Pelton,Forehand, Long & Wallace, 2008), Use of SEIM, Perceived Social Realism and Utility of SEIM (Peter & Valkenburg, 2006), and Sexual Behavior Inventory (Treboux & Busch-Rossnagel, 1990). All the instruments used in this study were translated to Malay language by using back to back translation and obtained high reliability. Descriptive, bivariate and multivariate analyses were used to present the data of the study. Bivariate analysis revealed that parental factors (sexual communication with parents and parental approval of sexual behavior), peers factors (perceived peers‟ behavior, sexual communication with peers and peers‟ approval of sexual behavior) and media factors (use of SEIM, perceived social realism and utility of SEIM) were significantly related to adolescents‟ sexual behavior. The results of regression analysis denoted that sexual communication with parents,perceived peers‟ sexual behavior and use of SEIM were significant contributors of adolescents‟ sexual behavior. Perceived peers‟ behavior appeared to be the strongest predictor of adolescents‟ sexual behavior. The findings of the study emphasized the importance of sexual socialization influences (parents, peer and media factors) on sexual behavior among Malaysian adolescents. Intervention and prevention programs to promote healthy sexuality among adolescents should emphasize on adolescents‟ socialization factors (parents, peers and media).